As geotecnologias no ensino de Geografia: análise das coleções didáticas do Ensino Médio do PNLD 2015 - Ribeiro, Carla Michelon (2018)
Geotechnologies are important tools of geoinformation used by different areas of knowledge: geography, agronomy, architecture, engineering, biology, among others. Aerial Photogrammetry, Remote Sensing (SR), Global Navigation Satellite System (GNSS), Geographic Information System (GIS) and Geoprocessing are some of the examples. In teaching, geotechnologies are also present, especially in the contents of the geography discipline. Geotechnologies appear as specific content in works destined to the beginning of high school and other levels, through texts, aerial images, satellite images, image charts, etc. Although geotechnologies already integrate the daily lives of a lot of citizens, it is a specific content and requires theoretical and practical knowledge for its use in geography teaching. In this context, the aim is to analyze the textbooks of high school geography approved by the Ministry of Education (MEC) of the National Textbook Program (PNLD) of 2015 and used in the colleges of the Regional Nucleus of Education of Toledo - PR. The analysis was based on the quantitative and qualitative methods using the technique of Content Analysis. The procedures include: I) Characterization and Identification of Didactic Collections using adapted criteria by Pontuschka, Paganelli and Cacete (2009); II) analysis of the specific content of geotechnologies and; III) analysis of the use of geotechnologies in the didactic collections. Considering that there are 8 (eight) collections of didactic works worked in the schools of the Regional Nucleus of Education of Toledo - PR, we have the analysis of 24 (twenty-four) textbooks. The results indicate that the structure of the books is distributed in units and chapters, however, there are collections that work with the geotechnologies in the beginning of the work, while others include it in the end. As for the analysis of the specific content, mistakes were identified that could lead to a distorted interpretation of geotechnologies. Regarding the analysis of the specific content, misconceptions were found that may lead to a distorted interpretation of geotechnologies, yet, some collections were also found that sought to associate geotechnologies with everyday examples, highlighting the importance of this technology in different areas of knowledge. In the analysis of the use of geotechnologies, it was identified that several contents in the three volumes of each collection use images, satellite images, aerial images, texts, schematics, etc., demonstrating the use of geotechnologies in other contents. Through the analysis it is understood that there are conceptual misunderstandings when portraying the term GNSS, however, several works show examples of applications that can contribute to the student’s understanding relating the content to the environment.